Trauma treatment factors contributing to efficiency - Widera-Wysoczańska, Agnieszka (Cambridge Scholars Publishing, 2016)
This book investigates the factors that contribute to the efficiency of psychological trauma treatment. Experts in the field explore the mechanisms of acute and interpersonal trauma, including partner violence, childhood abuse, elder abuse, natural disasters and war. New research investigates the characteristics of professional and non-professional helpers, victims and perpetrators, and the relationships between them, while crucial analyses shed light on the specific factors that influence the effectiveness of different interventions and psychotherapies. The question, 'can specific forms of ps.